Multilayer electronic component

By using the first glass of Ba, Zn and Si and the second glass of Ba and Si in the outer electrode of the multilayer ceramic capacitor, the molar ratio ratio is controlled, and the sealing problem caused by Si oxide is solved, and a high-reliability multilayer electronic assembly is achieved.

CN119724931APending Publication Date: 2025-03-28SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411340943.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2024-09-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The high softening temperature of Si oxide in the sintered electrode of the existing multi-layer ceramic capacitors leads to low wettability to copper, and the electrode gap cannot be fully filled, affecting the sealing property.

Method used

By using a first glass including Ba, Zn and Si in the interface layer of the outer electrode, and a second glass including Ba and Si in the base electrode layer, the average molar ratio (M1/M2) of the two is controlled to improve sealing and corrosion resistance.

Benefits of technology

It realizes effective sealing of external moisture or plating solution, and improves the reliability and moisture resistance of multi-layer electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724931A_ABST
    Figure CN119724931A_ABST
Patent Text Reader

Abstract

The present disclosure provides a multilayer electronic component including: a body including a dielectric layer and an internal electrode disposed on the dielectric layer; an external electrode disposed on the body and including a base electrode layer connected to the internal electrode; and an interface layer disposed between an end portion of the dielectric layer and the base electrode layer. The interface layer includes a first glass including Ba, Zn, and Si. The base electrode layer includes a second glass including Ba and Si. When the average molar ratio of Ba to Si (Ba / Si) contained in the first glass is M1 and the average molar ratio of Ba to Si (Ba / Si) contained in the second glass is M2, M1 and M2 satisfy M1 / M2 > = 1.5.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2023-0129208 filed on September 26, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field

[0002] The present disclosure relates to a multi-layer electronic assembly. Background Art

[0003] Multilayer ceramic capacitors (MLCC, a type of multilayer electronic component) are chip capacitors mounted on printed circuit boards of various electronic products such as video devices (such as liquid crystal displays (LCDs) and plasma display panels (PDPs)), computers, smart phones, and mobile phones for charging or discharging therefrom. Such multilayer ceramic capacitors are useful as components in various electronic devices due to their small size, high capacitance, and ease of mounting.

[0004] At present, sintered electrodes formed of metal (such as Cu) and glass are mainly used as external electrodes of multilayer ceramic capacitors. The metal component of the sintered electrode provides conductivity to the sintered electrode, while the glass provides adhesion between the sintered electrode and the body and can penetrate into the gaps within the sintered electrode to ensure sealing.

[0005] Generally, Si oxide, which is a network former, is used as a glass component of the sintered electrode. Si oxide has strong corrosion resistance and thus can prevent the glass from being corroded by the plating solution and the resulting penetration of the plating solution.

[0006] However, Si oxide has a high softening temperature and thus may have low wettability to copper (Cu). As a result, Si oxide may not be able to sufficiently fill voids in the sintered electrode, resulting in a problem in which the sealing of the sintered electrode cannot be ensured.

[0007] In order to prevent this problem, research is being conducted on external electrodes of multilayer ceramic capacitors that can ensure both corrosion resistance and sealing properties by appropriately adding oxides serving as network modifiers as glass components. Summary of the invention

[0008] An aspect of the present disclosure is to provide a multilayer electronic component having high reliability by preventing penetration of external moisture or plating solution.

[0009] According to one aspect of the present disclosure, a multilayer electronic component includes: a body including a dielectric layer and inner electrodes alternately arranged with the dielectric layer; an outer electrode arranged on the body and including a substrate electrode layer connected to the inner electrode; and an interface layer arranged between an end of the dielectric layer and the substrate electrode layer. The interface layer includes a first glass including Ba, Zn and Si. The substrate electrode layer includes a second glass including Ba and Si. When the average molar ratio of Ba to Si (Ba / Si) contained in the first glass is M1 and the average molar ratio of Ba to Si contained in the second glass is M2, M1 and M2 satisfy M1 / M2≥1.5. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The above and other aspects, features and advantages of the present disclosure will be more clearly understood through the following detailed description in conjunction with the accompanying drawings, in which: Figure 1 is a perspective view schematically showing a multilayer electronic component according to an embodiment; Figure 2 It is schematically shown Figure 1 An exploded perspective view of the subject; Figure 3 is a schematic diagram showing the Figure 1 A cross-sectional view of a section taken along line II'; Figure 4 is a schematic diagram showing the Figure 1 A cross-sectional view of a section taken along line II-II'; and Figure 5 yes Figure 3 Magnified view of area K1 in FIG. DETAILED DESCRIPTION

[0011] Hereinafter, embodiments of the present disclosure will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present disclosure may be modified in many different forms, and the scope of the present disclosure is not limited to the embodiments described below. In addition, the embodiments of the present disclosure are provided in order to more completely describe the present disclosure to those skilled in the art. Therefore, in order to explain more clearly, the shapes and sizes of the elements in the accompanying drawings may be exaggerated, and the elements represented by the same reference numerals in the accompanying drawings are the same elements.

[0012] In addition, in order to clearly describe the present disclosure, parts not related to the description are omitted in the drawings, and for the convenience of description, the size (e.g., thickness) of each component shown in the drawings is arbitrarily shown, and therefore, the present disclosure is not necessarily limited to the illustrated embodiments. In addition, the same reference numerals are used to describe components having the same functions within the scope of the same concept. In addition, throughout the specification, unless otherwise specified, when a component is referred to as "comprising", it means that it may also include other components without excluding other components.

[0013] In the drawings, a first direction may be defined as a thickness direction, a second direction may be defined as a length direction, and a third direction may be defined as a width direction.

[0014] Multilayer electronic components Figure 1 is a perspective view schematically showing a multilayer electronic component according to an embodiment.

[0015] Figure 2 It is schematically shown Figure 1 An exploded perspective view of the subject.

[0016] Figure 3 is a schematic diagram showing the Figure 1 A cross-sectional view of a section taken along line II'.

[0017] Figure 4 is a schematic diagram showing the Figure 1 A cross-sectional view of a section taken along line II-II'.

[0018] Figure 5 yes Figure 3 Magnified view of area K1 in FIG.

[0019] In the following, reference will be made to Figures 1 to 5 The multilayer electronic component 100 according to the embodiment is described in detail. In addition, a multilayer ceramic capacitor is described as an example of a multilayer electronic component, but the present disclosure is not limited thereto and the description may be applied to various multilayer electronic components such as an inductor, a piezoelectric element, a varistor, or a thermistor.

[0020] The multilayer electronic component 100 according to the embodiment may include a body 110 including a dielectric layer 111 and internal electrodes 121 and 122 , external electrodes 131 and 132 , and interface layers 141 and 142 .

[0021] There is no particular limitation on the specific shape of the body 110, but Figure 1As shown, the main body 110 may have a hexahedral shape or a shape similar to a hexahedron. Due to the shrinkage of the ceramic powder contained in the main body 110 during the sintering process or the polishing of the edges of the main body, the main body 110 may not have a perfect straight hexahedral shape but may generally have a hexahedral shape.

[0022] The main body 110 may have a first surface 1 and a second surface 2 that are opposite to each other in a first direction, a third surface 3 and a fourth surface 4 that are connected to the first surface 1 and the second surface 2 and are opposite to each other in a second direction, and a fifth surface 5 and a sixth surface 6 that are connected to the first surface 1, the second surface 2, the third surface 3, and the fourth surface 4 and are opposite to each other in a third direction.

[0023] The main body 110 may include a dielectric layer 111 and internal electrodes 121 and 122 that are alternately arranged with the dielectric layer 111. The plurality of dielectric layers 111 forming the main body 110 may be in a sintered state, and adjacent dielectric layers 111 may be integrated to the extent that it is difficult to identify the boundary between them without using a scanning electron microscope (SEM).

[0024] For example, the dielectric layer 111 may include a perovskite-type compound represented by ABO3 as a main component. The perovskite-type compound represented by ABO3 may be, for example, BaTiO3, (Ba 1-x Ca x )TiO3 (0 < x < 1) in which calcium (Ca), zirconium (Zr), etc. are partially solid-solved in BaTiO3, Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1), or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc.

[0025] For example, the internal electrodes 121 and 122 may be alternately arranged with the dielectric layer 111 in a first direction. The first internal electrode 121 and the second internal electrode 122 (a pair of electrodes with different polarities) may be arranged to face each other with the dielectric layer 111 interposed therebetween. The first internal electrode 121 and the second internal electrode 122 may be electrically separated from each other by the dielectric layer 111 provided therebetween.

[0026] The first internal electrode 121 is spaced apart from the fourth surface 4 and may be connected to a first external electrode 131 on the third surface 3. The second internal electrode 122 is spaced apart from the third surface 3 and may be connected to a second external electrode 132 on the fourth surface 4.

[0027] The conductive metal included in the internal electrodes 121 and 122 may be at least one of Ni, Cu, Pd, Ag, Au, Pt, Sn, W, Ti, and alloys thereof, and in more detail, the internal electrodes 121 and 122 may contain Ni as a main component, but the present disclosure is not limited thereto.

[0028] The average thickness td of the dielectric layer 111 does not need to be particularly limited, but may be, for example, 0.1 μm to 10 μm. The average thickness te of the internal electrodes 121 and 122 does not need to be particularly limited, but may be, for example, 0.05 μm to 3.0 μm. In addition, the average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 may be arbitrarily set according to the desired characteristics or uses. For example, in the case of a high-voltage automotive electronic component in order to obtain miniaturization and high capacitance, the average thickness td of the dielectric layer 111 may be less than 2.8 μm, and the average thickness te of the internal electrodes 121 and 122 may be less than 1 μm. In addition, in the case of a small-sized IT electronic component in order to obtain miniaturization and high capacitance, the average thickness td of the dielectric layer 111 may be 0.4 μm or less, and the average thickness te of the internal electrodes 121 and 122 may be 0.4 μm or less.

[0029] The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 refer to the average size of the dielectric layer 111 in the first direction and the average size of the internal electrodes 121 and 122 in the first direction, respectively. The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 can be measured by scanning the cross section of the body 110 in the first direction and the second direction at a magnification of 10,000 times with a scanning electron microscope (SEM). In more detail, the average thickness td of the dielectric layer 111 can be obtained by measuring the thickness at a plurality of points (for example, 30 points equally spaced in the second direction) of one dielectric layer 111 and then taking the average value thereof. In addition, the average thickness te of the internal electrodes 121 and 122 can be obtained by measuring the thickness at a plurality of points (for example, 30 points equally spaced in the second direction) of one internal electrode 121 or 122 and then taking the average value thereof. 30 equally spaced points can be specified in the capacitance forming portion Ac. On the other hand, if the thickness measurement is performed on 10 dielectric layers 111 and 10 internal electrodes 121 and 122, respectively, and then averaged, the average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 can be more generalized.

[0030] The body 110 may include a capacitor forming portion Ac and a first cover portion 112 and a second cover portion 113, the capacitor forming portion Ac is disposed inside the body 110 and includes a first internal electrode 121 and a second internal electrode 122, the first internal electrode 121 and the second internal electrode 122 are alternately disposed with a dielectric layer 111 interposed therebetween to form a capacitor, and the first cover portion 112 and the second cover portion 113 are disposed on the upper surface and the lower surface of the capacitor forming portion Ac opposite in the first direction, respectively. The cover portions 112 and 113 may be basically used to prevent damage to the internal electrode due to physical stress or chemical stress. The cover portions 112 and 113 may have the same configuration as the dielectric layer 111 except that the internal electrode is not included.

[0031] The average thickness tc of the covering portions 112 and 113 does not need to be particularly limited. For example, the average thickness tc of the covering portions 112 and 113 can be arbitrarily set according to the desired characteristics or uses. For example, in order to miniaturize the multilayer electronic component and increase the capacitance of the multilayer electronic component, the average thickness tc of the covering portions 112 and 113 can be 300μm or less, 100μm or less, 30μm or less, or 20μm or less, but the present disclosure is not limited thereto. In this case, the average thickness tc of the covering portions 112 and 113 refers to the average thickness of each of the first covering portion 112 and the second covering portion 113.

[0032] The average thickness tc of the covering parts 112 and 113 may refer to an average size of the covering parts 112 and 113 in the first direction, and may be an average value of the size in the first direction measured at five points equally spaced in a cross section of the body 110 in the first and second directions.

[0033] The body 110 may include a first edge portion 114 and a second edge portion 115, respectively disposed on both sides of the capacitance forming portion Ac that are opposite to each other in the third direction. For example, the edge portions 114 and 115 may refer to regions between both ends of the internal electrodes 121 and 122 and the outer surface of the body 110 in a cross section of the body 110 in the first direction and the third direction.

[0034] The edge portions 114 and 115 may include the same material as the dielectric layer 111 except that the internal electrodes 121 and 122 are not included. The edge portions 114 and 115 may substantially serve to prevent damage to the internal electrodes 121 and 122 due to physical stress or chemical stress.

[0035] The edge portions 114 and 115 may be formed by coating a conductive paste for the internal electrode on an area of ​​the ceramic green sheet other than an area where the edge portions are to be formed and then sintering. Alternatively, in order to suppress a step difference caused by the internal electrodes 121 and 122, after cutting is performed to expose the internal electrodes 121 and 122 to both sides of the capacitor forming portion Ac opposite to each other in the third direction, a single dielectric layer or two or more dielectric layers may be stacked on both sides of the capacitor forming portion Ac opposite to each other in the third direction, thereby forming the edge portions 114 and 115.

[0036] The average thickness tm of the edge portions 114 and 115 does not need to be particularly limited. For example, the average thickness tm of the edge portions 114 and 115 can be arbitrarily set according to the desired characteristics or uses. For example, in order to miniaturize the multilayer electronic component and increase the capacitance of the multilayer electronic component, the average thickness tm of the edge portions 114 and 115 can be 100 μm or less, 20 μm or less, or 15 μm or less, but the present disclosure is not limited thereto. In this case, the average thickness tm of the edge portions 114 and 115 refers to the average thickness of each of the first edge portion 114 and the second edge portion 115.

[0037] The average thickness tm of the edge portions 114 and 115 may refer to the average size of the edge portions 114 and 115 in the third direction, and may be the average value of the size of the edge portions 114 and 115 in the third direction measured at five equally spaced points in a cross-section of the body 110 in the first direction and the third direction.

[0038] The external electrodes 131 and 132 may be disposed on the third surface 3 and the fourth surface 4 of the body 110, and may extend over a portion of the first surface 1, a portion of the second surface 2, a portion of the fifth surface 5, and a portion of the sixth surface 6. The external electrodes 131 and 132 may include a first external electrode 131 disposed on the third surface 3 and a second external electrode 132 disposed on the fourth surface 4.

[0039] The external electrodes 131 and 132 may include substrate electrode layers 131a and 132a connected to the internal electrodes 121 and 122, respectively, and plating layers 131b and 132b disposed on the substrate electrode layers 131a and 132a, respectively. For example, the first external electrode 131 may include a first substrate electrode layer 131a connected to the first internal electrode 121 and a first plating layer 131b disposed on the first substrate electrode layer 131a, and the second external electrode 132 may include a second substrate electrode layer 132a connected to the second internal electrode 122 and a second plating layer 132b disposed on the second substrate electrode layer 132a.

[0040] The drawings show a structure in which the multilayer electronic component 100 has two external electrodes 131 and 132, but the structure is not limited thereto. The number or shape of the external electrodes 131 and 132 may be changed according to the shape or other uses of the internal electrodes 121 and 122.

[0041] The interface layers 141 and 142 may be disposed between the end of the dielectric layer 111 and the substrate electrode layers 131a and 132a. For example, the interface layers 141 and 142 may include a first interface layer 141 disposed between the third surface 3 and the first substrate electrode layer 131a and a second interface layer 142 disposed between the fourth surface 4 and the second substrate electrode layer 132a. The first interface layer 141 may be disposed in contact with the third surface 3, and the second interface layer 142 may be disposed in contact with the fourth surface 4. The interface layers 141 and 142 are disposed on the end of the dielectric layer 111, but may cover a portion of the internal electrodes 121 and 122. In addition, when observing the cross-section of the multilayer electronic component 100 in the first direction and the second direction, the interface layers 141 and 142 may completely cover the ends of one or more internal electrodes 121 and 122, but since the internal electrodes 121 and 122 also extend in the third direction, the base electrode layers 141a and 142a are in direct contact with the internal electrodes 121 and 122 to ensure the electrical connection between the internal electrodes 121 and 122 and the external electrodes 131 and 132.

[0042] In the following, reference will be made to Figure 5 The base electrode layer and the interface layer are described in more detail. Figure 5 The K1 region shown in FIG. 1 is an enlarged portion of the first substrate electrode layer 131 a and the first interface layer 141, but the first substrate electrode layer 131 a and the second substrate electrode layer 132 a have similar structures, and the first interface layer 141 and the second interface layer 142 have similar structures. Therefore, the description of the first substrate electrode layer 131 a and the first interface layer 141 can be applied to the description of the second substrate electrode layer 132 a and the second interface layer 142.

[0043] According to an embodiment, the interface layer 141 may include a first glass including Ba, Zn, and Si. Ba, Zn, and Si included in the first glass may each exist in the form of an oxide. The interface layer 141 may include the first glass as a main component, and may also partially include components included in the dielectric layer 111, the internal electrode 121, and / or the substrate electrode layer 131a. For example, the interface layer 141 may also include at least one of Mg, Al, Cu, Ca, B, and Sr.

[0044] The fact that the interface layer 141 includes the first glass as a main component means that the interface layer 141 does not include other metal components intentionally added except for the metal diffused from the internal electrode 121 and / or the base electrode layer 131a. Therefore, the interface layer 141 may include Ba, Zn, and Si as main components. In an embodiment, among the elements constituting the interface layer 141, the ratio of the total mole number of Ba, Zn, and Si to the total mole number of the remaining elements except oxygen may be 0.5 or more.

[0045] The substrate electrode layer 131a may include a metal 31. The metal 31 included in the substrate electrode layer 131a may include Cu, Ni, Ag, Pd, Al, Sn, and / or an alloy containing them. The metal 31 included in the substrate electrode layer 131a may include Cu, for example, may include Cu as a main component, but the present disclosure is not limited thereto.

[0046] The substrate electrode layer 131a may include a second glass 32. The second glass 32 may be dispersed in the metal 31. The second glass 32 may include Ba and Si, and in more detail, the second glass 32 may include Ba, Zn, and Si. Ba, Zn, and Si contained in the second glass may each exist in the form of an oxide. In an embodiment, at least a portion of the second glass 32 may be in contact with the first glass. As a result, the bonding strength between the substrate electrode layer 131a and the interface layer 141 may be improved.

[0047] As described above, Si contained in the first glass and the second glass acts as a network former and has strong corrosion resistance, and can prevent the glass from being corroded by the plating solution and the subsequent penetration of the plating solution. However, Si oxide has a high softening temperature and low wettability to metals such as Cu. Therefore, if the second glass 32 is formed only of Si oxide, the second glass 32 cannot fully fill the voids in the base electrode layer 131a, and these voids may be moisture penetration paths through which external moisture penetrates into the interior of the body 110.

[0048] Ba and Zn contained in the first glass and the second glass may function as a network modifier. Ba and Zn have lower corrosion resistance than Si, but may function to improve the sealing of the substrate electrode layer 131a and the interface layer 141 by lowering the softening temperature. In an embodiment, the first glass and the second glass may further include at least one of Al, Mg, Ca, and Sr. Al, Mg, Ca, and Sr may be used as a network modifier together with Ba and Zn.

[0049] On the other hand, since the substrate electrode layer 131a is disposed in contact with the plating layer 131b, the corrosion resistance of the second glass 32 included in the substrate electrode layer 131a may be more important than that of the first glass included in the interface layer 141, and accordingly, the second glass 32 may have a higher Si concentration (at%) than that of the first glass. Since the interface layer 141 is disposed more inner than the substrate electrode layer 131a, the interface layer 141 is not disposed in contact with the plating layer 131b, and the first glass may have a higher Ba concentration (at%) than the second glass 32 to achieve sealing.

[0050] Therefore, when the average molar ratio of Ba to Si (Ba / Si) contained in the first glass is M1 and the average molar ratio of Ba to Si (Ba / Si) contained in the second glass is M2, M1>M2 may be satisfied. For example, the interface layer 141 including the first glass having a relatively high average molar ratio of Ba to Si may effectively seal the surface of the body 110, and the base electrode layer 131a including the second glass having a relatively low average molar ratio of Ba to Si may effectively suppress the penetration of the plating solution.

[0051] According to an embodiment of the present disclosure, M1 and M2 may satisfy M1 / M2≥1.5. When M1 / M2 is 1.5 or greater, the corrosion resistance and sealing performance improvement effects of the present disclosure may be more significant. For example, if M1 is too low compared to M2, the sealing performance of the interface layer 141 may be deteriorated, and if M2 is too high compared to M1, the corrosion resistance of the substrate electrode layer 131a may be deteriorated.

[0052] The upper limit of M1 / M2 does not need to be particularly limited, but, for example, M1 / M2≤83 may be satisfied. If M1 / M2 is too high, the first glass of the interface layer 141 may be re-softened and moved away from its original position during the sintering process of the substrate electrode layer 131a, and thus the surface sealing performance of the body 110 may be deteriorated. In addition, if M1 / M2 exceeds 83, a significant difference in sintering behavior may occur due to the difference in softening temperature between the first glass and the second glass, which may reduce the corrosion resistance and sealing performance improvement effects in the present disclosure.

[0053] Each of M1 and M2 does not need to be particularly limited as long as M1 / M2 is 1.5 or greater. However, it is preferred that M1 is greater than or equal to 0.2 and less than or equal to 3.5. If M1 is less than 0.2, the sealing performance improvement effect of the present disclosure may be minimal, and if M1 is greater than 3.5, the above-mentioned re-softening phenomenon of the first glass may occur.

[0054] In addition, M2 may be greater than or equal to 0.01 and less than or equal to 0.2. If M2 is less than 0.01, the above-mentioned difference in sintering behavior may occur, and if M2 is greater than 0.2, the corrosion resistance improvement effect of the present disclosure may be minimal.

[0055] An example of a method for measuring M1 and M2 will be described. First, an image of a cross section of the multilayer electronic component 100 in the first direction and the second direction (through the center of the multilayer electronic component 100 in the third direction) is obtained using a scanning electron microscope (SEM). Next, at any point in the first glass, after measuring the content (at%) of the Si element and the content (at%) of the Ba element by energy dispersive spectroscopy (EDS), the measured content of the Ba element is divided by the content of the Si element to obtain the molar ratio of Ba to Si. After these EDS measurements are performed at five or more random points in the first glass, M1 can be obtained by taking the average value of the measured molar ratios of Ba to Si. In addition, at any point in the second glass, after measuring the content (at%) of the Si element and the content (at%) of the Ba element by energy dispersive spectroscopy (EDS), the measured content of the Ba element can be divided by the content of the Si element to obtain the molar ratio of Ba to Si. After these EDS measurements are performed at five or more random points in the second glass, M2 can be obtained by taking the average value of the measured molar ratios of Ba to Si.

[0056] In an embodiment, an average molar ratio of Zn to Si (Zn / Si) included in the first glass may be greater than an average molar ratio of Zn to Si (Zn / Si) included in the second glass. Like Ba, Zn may play a role in achieving sealing performance. For example, the interface layer 141 including the first glass having a relatively high average molar ratio of Zn to Si may effectively seal the surface of the body 110, and the base electrode layer 131a including the second glass having a relatively low average molar ratio of Zn to Si may effectively suppress the penetration of the plating solution.

[0057] The thickness of the interface layer 141 does not need to be particularly limited. However, it may be desirable that the average thickness ti of the interface layer 141 is greater than 2 μm and less than or equal to 8 μm. If the average thickness ti of the interface layer 141 is 2 μm or less, the effect of improving the sealing performance in the present disclosure may be negligible. In addition, if the average thickness ti of the interface layer 141 is greater than 8 μm, the electrical connectivity between the internal electrode 121 and the substrate electrode layer 131 a may be reduced, and accordingly, there is a risk that the capacitance of the multilayer electronic component 100 may be reduced. The average thickness ti of the interface layer 141 refers to the average size of the interface layer 141 in the second direction. The average thickness ti of the interface layer 141 can be measured by obtaining an image of a cross section of the multilayer electronic component 100 in the first and second directions (through the center of the multilayer electronic component 100 in the third direction) using a scanning electron microscope (SEM), and then measuring the thickness of the interface layer 141 at multiple points (for example, five points equally spaced in the first direction) of the interface layer 141 disposed on one dielectric layer 111, and then taking the average value thereof. In addition, if these thickness measurements are performed on the respective interface layers 141 disposed on five or more dielectric layers 111 (eg, measured at a total of 25 or more points) and then averaged, the average thickness of the interface layer 141 can be more generalized.

[0058] The plating layers 131b and 132b can improve the mounting characteristics. The types of the plating layers 131b and 132b are not particularly limited, and may be plating layers containing Ni, Sn, Pd, Cu and / or their alloys, and may be formed by a plurality of layers. The plating layers 131b and 132b may be, for example, Ni plating layers or Sn plating layers, or may be formed by sequentially forming Ni plating layers and Sn plating layers. In addition, the plating layers 131b and 132b may include a plurality of Ni plating layers and / or a plurality of Sn plating layers.

[0059] On the other hand, although not shown, a conductive resin layer containing metal and resin may be provided between the base electrode layer 131 a and the plated layer 131 b and between the base electrode layer 132 a and the plated layer 132 b , if necessary.

[0060] The overall size of the multilayer electronic component 100 does not need to be particularly limited. For example, the size of the multilayer electronic component 100 in the second direction may be 0.1 mm to 4.5 mm, the size of the multilayer electronic component 100 in the third direction may be 0.05 mm to 3.2 mm, and the size of the multilayer electronic component 100 in the first direction may be 0.05 mm to 2.5 mm.

[0061] Hereinafter, an example of a method of manufacturing the above-described multilayer electronic component 100 will be described.

[0062] First, a ceramic powder forming the dielectric layer 111 is prepared. Examples of the ceramic powder may include BaTiO3 powder, etc. For example, BaTiO3 powder may be synthesized by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate. For example, methods for synthesizing ceramic powder include a solid phase method, a sol-gel method, a hydrothermal synthesis method, etc., but the present disclosure is not limited thereto.

[0063] Next, after the prepared ceramic powder is dried and pulverized, a ceramic slurry may be prepared by mixing it with an organic solvent such as ethanol and a binder such as polyvinyl butyral, and the ceramic slurry is coated on a carrier film and dried to prepare a ceramic green sheet.

[0064] Next, an internal electrode pattern is formed by printing a conductive paste for internal electrodes containing metal powder, a binder, etc., on the ceramic green sheet with a predetermined thickness using a screen printing method or a gravure printing method.

[0065] Then, after the ceramic green sheet on which the internal electrode pattern is printed is peeled off from the carrier film, a ceramic laminate is formed by stacking the ceramic green sheets on which the internal electrode pattern is printed by a predetermined number of layers and pressing. The ceramic laminate is cut into sheets having a predetermined sheet size. In detail, the adhesive contained in the cut sheet, etc., can be removed by an adhesive removal process. The conditions of the adhesive removal process may vary depending on the type of adhesive used and are not particularly limited. Thereafter, the sheet from which the adhesive has been removed may be sintered at a temperature greater than or equal to 1000° C. and less than or equal to 1400° C. to form a body 110 including a dielectric layer 111 and internal electrodes 121 and 122.

[0066] Next, an interface layer paste (i.e., a paste for an interface layer) obtained by mixing the first glass frit, the binder, and the solvent is applied to the third surface 3 and the fourth surface 4 of the body 110 and then sintered, thereby forming the interface layers 141 and 142. The method of applying the paste for the interface layer to the body 110 does not need to be particularly limited, and a known method such as dipping, transfer, and deposition may be used.

[0067] The first glass frit may include BaO, ZnO and SiO2, and may further include Al2O3, MgO, CaO, SrO, etc., if necessary. In this case, the content of BaO and SiO2 added to the interface layer paste may be adjusted, for example, so that the average Ba / Si molar ratio (M1) of the interface layers 141 and 142 after sintering is 0.2 to 3.5. For example, based on 100 moles of the first glass frit, BaO may be 5 to 50 moles, ZnO may be 1 to 40 moles, and SiO2 may be 5 to 15 moles, but the present disclosure is not limited thereto. The paste for the interface layer may be sintered at a temperature of, for example, 550°C to 750°C.

[0068] Before forming the substrate electrode layers 131a and 132a, in order to make the internal electrodes 121 and 122 and the substrate electrode layers 131a and 132a contact each other, both surfaces in the second direction of the body 110 on which the interface layers 141 and 142 are formed may be polished. The method of polishing both surfaces in the second direction of the body 110 on which the interface layers 141 and 142 are formed does not need to be particularly limited, but for example, a method such as barrel polishing, sandblasting, and / or laser polishing may be used.

[0069] Then, the substrate electrode layers 131a and 132a may be formed by coating a substrate electrode layer paste (i.e., a paste for the substrate electrode layer) containing a mixture of metal powder, a second glass frit, a binder, and a solvent on the interface layers 141 and 142 and then sintering. The second glass frit may include BaO, ZnO, and SiO2, and may further include Al2O3, MgO, CaO, SrO, etc., if necessary. In this case, the content of BaO and SiO2 added to the substrate electrode layer paste may be adjusted so that the Ba / Si molar ratio of the sintered substrate electrode layers 131a and 132a is, for example, greater than or equal to 0.01 and less than or equal to 0.2. For example, based on 100 moles of the second glass frit, BaO may be 1 mole to 10 moles, ZnO may be 1 mole to 10 moles, and SiO2 may be 30 moles to 70 moles, but the present disclosure is not limited thereto. On the other hand, since the paste for the base electrode layer has a higher SiO2 content than the paste for the interface layer, it may be desirable to sinter the paste for the base electrode layer at a higher temperature than the temperature at which the paste for the interface layer is sintered, for example, sintering the paste for the base electrode layer at a temperature of 750°C to 900°C, but the present disclosure is not limited thereto.

[0070] The method of forming the plating layers 131 b and 132 b does not need to be particularly limited, and for example, electrolytic plating and / or electroless plating may be used.

[0071] However, the above manufacturing method is an example, and the method of manufacturing the multilayer electronic component 100 is not limited to the above manufacturing method.

[0072] (Experimental example) <Reliability evaluation based on M1 / M2> The following sample No. 1 was manufactured in the following manner. First, a ceramic slurry was prepared by mixing BaTiO3 powder, an organic solvent (such as ethanol) and a binder (such as polyvinyl butyral), and then the ceramic slurry was coated on a carrier film and dried to prepare a ceramic green sheet. Next, an internal electrode pattern was formed by printing a conductive paste for internal electrodes containing Ni powder, a binder, etc. on the ceramic green sheet at a predetermined thickness, and the ceramic green sheets on which the internal electrode pattern was formed were stacked and cut. Thereafter, a binder removal process and a sintering process were performed on the stacked sheets to form a body.

[0073] Thereafter, an interface layer paste obtained by mixing the first glass frit, a binder, and a solvent is applied to the third surface 3 and the fourth surface 4 of the body 110 and then sintered at 650° C. to 750° C., thereby forming interface layers 141 and 142. In the case where BaO, ZnO, and SiO2 are included in the paste for the interface layer, BaO is 5 to 50 mol, ZnO is 1 to 40 mol, and SiO2 is 5 to 15 mol based on 100 mol of the first glass frit.

[0074] Next, a base electrode layer paste obtained by mixing Cu powder, a second glass frit, a binder and a solvent is coated on the interface layer and then sintered at 700° C. to 850° C. to form a base electrode layer. In the case where BaO, ZnO and SiO2 are contained in the paste for the base electrode layer, BaO is 1 to 10 mol, ZnO is 1 to 10 mol, and SiO2 is 30 to 70 mol based on 100 mol of the second glass frit.

[0075] Then, Ni plating and Sn plating were sequentially formed on the base electrode layer to prepare a sample piece of sample number 1. The sample piece of sample number 1 with a capacitance of 10 μF was manufactured with a 2012 size (about 2.0 mm in the second direction and about 1.2 mm in the third direction).

[0076] Samples No. 2 to 8 were prepared in the same manner as Sample No. 1 (wherein the ranges of the contents of BaO, ZnO, and SiO2 contained in the paste for the interface layer and the paste for the base electrode layer in Sample No. 2 to 8 were the same as those in Sample No. 1), while the contents of BaO, ZnO, and SiO2 added to the paste for the interface layer were changed so that the average molar ratio (M1) of Ba / Si in the interface layer after sintering was different from the average molar ratio (M1) of Ba / Si in the interface layer after sintering of Sample No. 1. In detail, from Sample No. 2 to Sample No. 8, the content of BaO increased compared with SiO2 added to the interface layer paste.

[0077] Thereafter, after obtaining an image by photographing a cross section of the sample piece of each sample number in the first direction and the second direction (through the center of the sample piece in the third direction) with a scanning electron microscope (SEM), the molar ratio of Ba to Si is measured by performing energy dispersive spectroscopy (EDS) on the first glass included in the interface layer. After performing this EDS measurement at five random points in the first glass, M1 is obtained by taking the average value of the measured molar ratio of Ba to Si. In the same manner, EDS measurement is performed at five random points in the second glass included in the base electrode layer, and then M2 is obtained by taking the average value of the measured molar ratio of Ba to Si. Thereafter, the M1 / M2 values ​​of the sample pieces of each sample number are listed in Table 1 below.

[0078] After that, a voltage of 1.5 Vr was applied to 20 sample pieces of each sample number at a temperature of 85°C and a relative humidity of 85% for 24 hours to perform reliability evaluation, and the case where one or more sample pieces had an insulation resistance (IR) value drop to 10% or less of the initial IR value was marked with "X", and the case where no sample piece had an insulation resistance (IR) value drop to 10% or less of the initial IR value was marked with "○".

[0079] [Table 1]

[0080] Referring to Table 1 above, it can be confirmed that Sample Nos. 3 to 7, where M1 / M2 is 1.5 or more, do not cause defects when evaluating moisture resistance reliability. This is because the interface layer seals the surface of the body and prevents external moisture from penetrating into the inside of the body. However, it can be confirmed that Sample Nos. 1 to 2, where M1 / M2 is less than 1.5, and Sample No. 8, where M1 / M2 is greater than 83, have defects when evaluating moisture resistance reliability.

[0081] <Reliability evaluation according to thickness of interface layer> In order to evaluate the reliability according to the thickness of the interface layer, sample sheets of sample numbers 9 to 13 were manufactured. First, sample number 9 was manufactured in the same manner as sample number 1, but the base electrode layer was directly formed without applying the paste for the interface layer.

[0082] Sample numbers 10 to 13 were prepared in the same manner as sample number 6, and M1 / M2 was 16.0. However, the coating amount of the interface layer paste was adjusted for each sample number so that the average thickness of the interface layer after sintering was different from each other. The average thickness of the interface layer was obtained by obtaining an image of a cross section of a multilayer electronic component in the first direction and the second direction (through the center of the multilayer electronic component in the third direction) using a scanning electron microscope (SEM), and then measuring the thickness at five equally spaced points in the first direction in the interface layer set on one dielectric layer 111 to obtain its average value. In addition, the measurement of the average thickness was performed on the interface layer set on five dielectric layers 111, and the average thickness of the interface layer 141 measured at a total of 25 points is listed in Table 2 below.

[0083] After that, the capacitance and reliability evaluation of the sample pieces of each sample number are performed. First, the capacitance of 30 sample pieces of each sample number is measured using an LCR meter. Among the 30 sample pieces, the case where one or more sample pieces with a measured capacitance less than 95% of the nominal capacitance are marked as "X", and the case where no sample piece with a measured capacitance less than 95% of the nominal capacitance is marked as "○". The reliability evaluation is performed in the same manner as the above method, and the case where one or more defective samples with an insulation resistance (IR) value dropping to 10% or less of the initial IR value are marked as "X", and the case where no defective sample with an insulation resistance (IR) value dropping to 10% or less of the initial IR value is marked as "○".

[0084] [Table 2]

[0085] Referring to Table 2 above, it can be confirmed that when the average thickness of the interface layer is 2 μm or less, poor samples appear in the moisture resistance reliability evaluation. This is because the interface layer does not fully seal the surface of the main body. In addition, it can be seen that when the average thickness of the interface layer exceeds 8 μm, the capacitance is reduced to less than 95% of the nominal capacitance. Therefore, it can be seen that the average thickness of the interface layer is preferably greater than 2 μm and less than or equal to 8 μm.

[0086] As described above, a highly reliable multilayer electronic component can be provided by preventing penetration of external moisture or plating solution.

[0087] The present disclosure is not limited by the above-mentioned embodiments and drawings, but is intended to be limited by the appended claims. Therefore, within the scope of the technical spirit of the present disclosure described in the claims, those skilled in the art will be able to make various forms of replacement, modification and change, and this will also be considered to fall within the scope of the present disclosure.

[0088] In addition, the expression "embodiment" does not indicate the same embodiment, and is provided to emphasize and describe different unique features. However, the embodiment presented above does not exclude implementation in combination with features of another embodiment. For example, even if a matter described in a specific embodiment is not described in another embodiment, it can be understood as a description related to another embodiment, unless there is a description contrary to or contradictory to the matter in another embodiment.

[0089] In addition, expressions such as first and second are used to distinguish one component from another component, and do not limit the order and / or importance of the components. In some cases, without departing from the scope of the rights, the first element may be named the second element, and similarly, the second element may be named the first element.

[0090] While example embodiments have been shown and described above, it will be readily apparent to those skilled in the art that modifications and variations may be made without departing from the scope of the present disclosure as defined by the appended claims.

Claims

1. A multilayer electronic component comprising: a main body, comprising a dielectric layer and an inner electrode disposed on the dielectric layer; an external electrode disposed on the body and comprising a base electrode layer connected to the internal electrode; as well as an interface layer disposed between the end of the dielectric layer and the base electrode layer, wherein the interface layer comprises a first glass containing Ba, Zn and Si, The base electrode layer includes a second glass containing Ba and Si, and When the average molar ratio of Ba to Si contained in the first glass is M1 and the average molar ratio of Ba to Si contained in the second glass is M2, M1 and M2 satisfy M1 / M2≥1.

5.

2. The multilayer electronic component of claim 1, wherein: M1 is greater than or equal to 0.2 and less than or equal to 3.

5.

3. The multilayer electronic component of claim 1, wherein: M2 is greater than or equal to 0.01 and less than or equal to 0.

2.

4. The multilayer electronic component of claim 1, wherein: M1 and M2 satisfy M1 / M2≤83.

5. The multilayer electronic component of claim 1, wherein: The average thickness of the interface layer is greater than 2 μm and less than or equal to 8 μm.

6. The multilayer electronic component of claim 1, wherein: The second glass further includes Zn, and An average molar ratio of Zn to Si contained in the first glass is greater than an average molar ratio of Zn to Si contained in the second glass.

7. The multilayer electronic component of claim 1, wherein: At least a portion of the second glass is in contact with the first glass.

8. The multilayer electronic component of claim 1, wherein: The first glass and the second glass each further include at least one of Al, Mg, Ca, and Sr.

9. The multilayer electronic component of claim 1, wherein: Among the elements constituting the interface layer, a ratio of the total number of moles of Ba, Zn, and Si to the total number of moles of the remaining elements excluding oxygen is 0.5 or more.

10. The multilayer electronic component of claim 1, wherein: The base electrode layer includes a metal including Cu.

11. The multilayer electronic component of claim 1, wherein: The external electrode further includes a plating layer disposed on the base electrode layer.

12. The multilayer electronic component of claim 1, wherein: The base electrode layer is in direct contact with the internal electrode.

13. A multilayer electronic component comprising: Dielectric layer; an inner electrode disposed on the dielectric layer; an external electrode disposed on side surfaces of the dielectric layer and the internal electrode and including a base electrode layer including a second glass; as well as an interface layer disposed at an interface between the dielectric layer and the base electrode layer and comprising a first glass, The first glass and the second glass include Ba, Si and Zn, and the average molar ratio of Zn to Si in the first glass is greater than the average molar ratio of Zn to Si in the second glass.

14. The multilayer electronic component of claim 13, wherein: An average molar ratio of Ba to Si contained in the first glass is M1 and an average molar ratio of Ba to Si contained in the second glass is M2, and M1 and M2 satisfy 1.5≤M1 / M2≤83.

15. The multilayer electronic component of claim 13, wherein: The first glass covers the entire side surface of the dielectric layer and a portion of the internal electrode.

16. The multilayer electronic component of claim 13, wherein: The average thickness of the interface layer is in the range of 2.0 μm to 8.0 μm.

17. The multilayer electronic component of claim 13, wherein: The base electrode layer includes a metal including Cu.

18. The multilayer electronic assembly of claim 13, wherein: The first glass and the second glass further include Al, Mg, Ca, Sr or a combination thereof.

Citation Information

Patent Citations

  • Heater assembly and aerosol generating device including the same

    KR1020230129208A